Magnetic structure and exchange interactions in quasi-1D MnCl(2)(urea)(2) - Manson, Jamie L. (Inorg Chem, 2015)
MnCl(2)(urea)(2) is a new linear chain coordination polymer that exhibits slightly counter-rotated MnCl(4) rhomboids along the chain-axis. The material crystallizes in the non-centrosymmetric orthorhombic space group Iba2, with each Mn(II) ion equatorially surrounded by four Cl(−) that lead to bi-bridged ribbons. Urea ligands coordinate via O-atoms in the axial positions. Hydrogen bonds of the Cl⋯H-N and O⋯H-N type link the chains into a quasi-3D network. Magnetic susceptibility data reveal a broad maximum at 9 K that is consistent with short-range magnetic order. Pulsed-field magnetization measurements conducted at 0.6 K show that a fully polarized magnetic state is achieved at B(sat) = 19.6 T with a field-induced phase transition occurring at 2.8 T. Neutron diffraction studies made on a powdered sample of MnCl(2)(urea)(2) reveal that long-range magnetic order occurs below T(N) = 3.2(1) K. Additional Bragg peaks due to antiferromagnetic (AFM) ordering can be indexed according to the Ib’a2’ magnetic space group and propagation vector τ = [0, 0, 0]. Rietveld profile analysis of these data reveal a Néel-type collinear ordering of Mn(II) ions with an ordered magnetic moment of 4.06(6) μ(B) (5 μ(B) is expected for isotropic S = 5/2) oriented along the b-axis, i.e., perpendicular to the chain-axis that runs along the c-direction. Owing to potential for spatial exchange anisotropy and the pitfalls in modeling bulk magnetic data, we analyzed inelastic neutron scattering data to retrieve the exchange constants; J(c) = 2.22 K (intrachain), J(a) = −0.10 K (interchain) and D = −0.14 K with J > 0 assigned to AFM coupling. This J configuration is most unusual and contrasts the more commonly observed case of AFM-coupled FM-chains.